2013
DOI: 10.1038/mt.2013.14
|View full text |Cite
|
Sign up to set email alerts
|

Rescue of Impaired NK Cell Activity in Hodgkin Lymphoma With Bispecific Antibodies In Vitro and in Patients

Abstract: Natural killer (NK) cells represent a key component of the innate immune system against cancer. Nevertheless, malignant diseases arise in immunocompetent individuals despite tumor immunosurveillance. Hodgkin lymphoma (HL) is characterized by CD30+ tumor cells and a massive infiltration of immune effector cells in affected lymph nodes. The latter obviously fail to eliminate the malignant cell population. Here, we tested for functional NK cell defects in HL and suggest an improvement of NK function by therapeuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(68 citation statements)
references
References 49 publications
3
63
0
2
Order By: Relevance
“…Decreased NK cell cytotoxicity has been observed in many patients suffering from tumors or immunosuppressive diseases (Ziegler et al, 1981;Sirianni et al, 1990;DanielouLazareth et al, 2013;Reiners et al, 2013). Our results indicate that SMG can significantly inhibit the cytotoxicity of NK cells ( p < 0.05).…”
Section: Discussionsupporting
confidence: 67%
“…Decreased NK cell cytotoxicity has been observed in many patients suffering from tumors or immunosuppressive diseases (Ziegler et al, 1981;Sirianni et al, 1990;DanielouLazareth et al, 2013;Reiners et al, 2013). Our results indicate that SMG can significantly inhibit the cytotoxicity of NK cells ( p < 0.05).…”
Section: Discussionsupporting
confidence: 67%
“…This effect was transient, and total NK-cell numbers were back to baseline levels prior to the next infusion (data not shown). In parallel, the relative portion of activated NK cells, indicated by CD69 1 , increased immediately after the infusions, as reported previously by Reiners et al 25 This observation was dose independent and strongest after the first infusion. However, during the period between the infusions, activated NK cells decreased again to baseline levels prior to the next infusion.…”
Section: Response To Treatmentsupporting
confidence: 73%
“…34,35 Poppema et al have demonstrated that specific cytotoxic T-or NK-cell populations are absent in the environment of H/RS cells. 36 Reiners et al 25 investigated functional NK-cell defects and found that in peripheral blood of HL patients, NKcell function is impaired. This impairment correlated with the downregulation of the NK-cell receptors NKp30 and, in particular, NKG2D.…”
Section: Discussionmentioning
confidence: 99%
“…However, this might be different in other tumor entities (eg, acute myeloid leukemia 16 or Hodgkin lymphoma). 45 The only variation reported so far for NK cells from CLL patients compared with NK cells from healthy donors is a slight but significant down-regulation of NKp30. 15 A decreased expression of NCRs on NK cells correlating to poor prognostic factors was also reported.…”
Section: Discussionmentioning
confidence: 99%